2007
DOI: 10.1039/b707517k
|View full text |Cite
|
Sign up to set email alerts
|

Light-fluorous safety-catch arylgermanes ? exceptionally robust, photochemically activated precursors for biaryl synthesis by Pd(0) catalysed cross-coupling

Abstract: A new class of arylgermane derivative that participate efficiently in Pd(0)-catalysed cross-coupling reactions with aryl bromides following photochemical activation is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 23 publications
(7 reference statements)
0
42
0
Order By: Relevance
“…Although in recent years a number of alternative transition metal-catalyzed cross-coupling protocols for the synthesis of the initial 4'-chloro-2-nitrobiphenyl intermediate 3 have been disclosed in the literature, [9][10][11][12][13][14] our continuous-flow route toward Boscalid is based on the original Suzuki-Miyaura BASF strategy (Scheme 1) as this appeared to be the most practical and economical route. Following the "microwave-to-flow" optimization paradigm, [15,16] all three reaction steps were first investigated on a small scale using sealed vessel batch microwave heating as a process intensification method in order to derive at the shortest possible reaction times, a prerequisite for achieving high throughput in continuous-flow synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in recent years a number of alternative transition metal-catalyzed cross-coupling protocols for the synthesis of the initial 4'-chloro-2-nitrobiphenyl intermediate 3 have been disclosed in the literature, [9][10][11][12][13][14] our continuous-flow route toward Boscalid is based on the original Suzuki-Miyaura BASF strategy (Scheme 1) as this appeared to be the most practical and economical route. Following the "microwave-to-flow" optimization paradigm, [15,16] all three reaction steps were first investigated on a small scale using sealed vessel batch microwave heating as a process intensification method in order to derive at the shortest possible reaction times, a prerequisite for achieving high throughput in continuous-flow synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…[21,22] For the selective reduction of the nitro group in 4'-chloro-2-nitrobiphenyl (3) we have envisaged a heteroA C H T U N G T R E N N U N G geneous transition metal-catalyzed hydrogenation protocol as these methods generally can be easily transformed into a scalable continuous-flow process employing a fixed-bed catalyst reactor. [23] To the best of our knowledge, in the context of the synthesis of Boscalid such an approach has never been considered, and most of the published methods employ more traditional reducing agents such as SnCl 2 [10,12] or Fe/NH 4 Cl. [13] Following the "microwave-to-flow" optimization regime, initial experiments were carried out in a batch microwave reactor.…”
mentioning
confidence: 99%
“…Without purification, these difluorogermanes were immediately subject to Pd(0)-catalyzed cross-coupling with a selection of aryl bromides again under the conditions previously developed for biaryl coupling (Table 1). 3 In all cases, moderate to good yields of isolated styrenyl products 5 were obtained, and a single major ¢-substituted isomer predominated although the coupling of germane 3a with relatively electron-rich aryl bromides resulted in the formation of significant amounts of the ¡-substituted isomers (i.e., products of cine cross-coupling, Entries 68). Assignment of the stereochemistry of the major (E)-and minor (Z)-¢-substituted styrenes was straightforward on the basis of Ar C 8 F 17 Ge 2-Nap 2-Nap R C 8 F 17 Ge H NMR spectra due to the two protons being close in chemical shift; this gave these spectra a very distinctive appearance and prevented assignment by alkene 3 J value analysis.…”
mentioning
confidence: 99%
“…Assignment of the product stereochemistries as (E) followed from 1 H NMR analysis of their vicinal alkenyl coupling constants ( 3 J µ 18 Hz). Photolytic activation of (E)-alkenylgermanes 3a3c under the conditions developed previously by us for arylgermanes 3 resulted in smooth conversion to the corresponding (E)-alkenyldifluorogermanes 4a4c. An alkenyl 3 J value of µ18 Hz in the 1 H NMR spectrum of derivative 4a confirmed that no photoisomerization had occurred.…”
mentioning
confidence: 99%
See 1 more Smart Citation